Why a mathematics teacher studies a master’s degree in Mathematics Education - Molina Zavaleta, Juan Gabriel; Rosas Mendoza, Alejandro Miguel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
A study of in-service mathematics teachers motivation to pursue a master degree in Mathematics Education is presented. The research was carried out by analyzing the files of four admission processes. 316 cases between the years 2018-2021 were considered. During an interview, participants responded to the question “Why did you decide to study the Master in Science in Mathematics Education degree?” The outcomes indicated the most declared reason was to seek professional development; this predominant response was maintained across these years (except for 2019). Other popular reasons included the master degree modality, institutional prestige, and pleasure in teaching mathematics.